Analysis of the Effect of Boiling Time on Oil Yield Palm oil at PTPN IV Mayang Plantation - Luat Surya Napitupulu; Tambos August Sianturi (Journal of Engineering Science and Technology Management, 2026)
The boiling process of fresh fruit bunches (FFB) at PTPN IV Kebun Mayang is carried out using a semi-automatic system using a horizontal steam pressure sterilizer. This study analyzed three boiling time programs, namely 85 minutes, 90 minutes, and 95 minutes, with a triple peak pressure system. The purpose of the study was to determine the most optimal boiling time to obtain the potential palm oil yield. The method used was a direct experiment with quantitative and qualitative observations of the potential of fresh fruit bunches (FFB) and oil yield. The results showed that the average RMS of the 85-minute experiment was 16.98%, the average RMS of the 90-minute experiment was 23.76%, and the average RMS of the 95-minute experiment was 19.44%. In conclusion, the 90-minute boiling time appears to provide the most balanced results. Boiling that is too short results in low yields while boiling that exceeds the optimum limit also tends to reduce the quality or amount of extractable yield.